2009
DOI: 10.1111/j.1463-1318.2009.01789.x
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced recovery in colorectal resections: a systematic review and meta‐analysis1

Abstract: Enhanced recovery programmes after colorectal resections reduce length-of-stay and may reduce 30 days morbidity and increase 30 days readmission without increasing mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 21 publications
(46 reference statements)
0
67
1
3
Order By: Relevance
“…Recently, the introduction of enhanced recovery after surgery (ERAS) protocols has revolutionized preoperative and postoperative care (19,20). Evidence suggests that these methods are associated with a reduced hospital stay and minimal morbidity, without affecting patient care, particularly in patients undergoing colorectal surgery (19). Similarly, in esophageal cancer, we believe that the availability of the ERAS protocol, including respiratory rehabilitation, affects postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the introduction of enhanced recovery after surgery (ERAS) protocols has revolutionized preoperative and postoperative care (19,20). Evidence suggests that these methods are associated with a reduced hospital stay and minimal morbidity, without affecting patient care, particularly in patients undergoing colorectal surgery (19). Similarly, in esophageal cancer, we believe that the availability of the ERAS protocol, including respiratory rehabilitation, affects postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Chumillas et al reported the result of a single blind randomized clinical trial of 81 patients following upper abdominal surgery and showed that the incidence of postoperative pulmonary complications was 7.5% in the rehabilitation group and 19.5% in the control group (18). Recently, the introduction of enhanced recovery after surgery (ERAS) protocols has revolutionized preoperative and postoperative care (19,20). Evidence suggests that these methods are associated with a reduced hospital stay and minimal morbidity, without affecting patient care, particularly in patients undergoing colorectal surgery (19).…”
Section: Discussionmentioning
confidence: 99%
“…The colorectal guideline from the Enhanced Recovery After Surgery (ERAS) Society (Kista, Sweden) has been widely studied internationally [1][2][3][4][5][6] , with most centres achieving significant outcome effects, including a reduction in length of stay [los (2.5 days on average)], a decline in complications [5][6][7][8] , and cost benefits to the system [mean savings of €1651 (US$2245) per patient] 4,9,10 . We recently used the Alberta Health Services ERAS Implementation Program to implement the eras guideline across Alberta, achieving similar health-system benefits 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several randomized trials have confirmed these findings and are summarised in a systematic review incorporating 512 patients [15]. Primary hospital stay and morbidity were significantly lower for patients on enhanced recovery programmes.…”
Section: Evidencementioning
confidence: 52%
“…Enhanced recovery programmes appear to be safe and shorten hospital stay after elective colorectal surgery. These programmes reduce overall complication rates, especially cardiopulmonary complications [15].…”
Section: Evidencementioning
confidence: 99%